A Strategy for Risk-adjusted Ranking of Surgeons and Practices Based on Patient-reported Outcomes After Elective Lumbar Surgery. Issue 9 (1st May 2019) - Sivaganesan, Ahilan; Asher, Anthony L.; Bydon, Mohamad; Khan, Inamullah; Kerezoudis, Panagoitis; Foley, Kevin T.; Nian, Hui; Harrell, Frank E.; Archer, Kristin R.; Devin, Clinton J.
Abstract : Study Design: This study retrospectively analyzes prospectively collected data. Objective: The primary aim of this study is to present a scheme for patient-reported outcome (PRO)-based, risk-adjusted rankings of spine surgeons and sites that perform elective lumbar surgery, using the Quality and Outcomes Database (QOD). Summary of Background Data: There is currently no means of determining which spine surgeons or centers are positive or negative outliers with respect to PROs for elective lumbar surgery. This is a critical gap as we move toward a value-based model of health care in which providers assume more accountability for the effectiveness of their treatments. Methods: Random effects regression models were fit for the following outcomes, with QOD site as a fixed effect but surgeon ID as a random effect: Oswestry Disability Index, EQ-5D, back pain and leg pain, and satisfaction. Hierarchical Bayesian models were also fit for each outcome, with QOD site as a random effect and surgeon as a nested random effect. Results: Our study cohort consists of 8834 patients who underwent surgery by 124 QOD surgeons, for the degenerative lumbar diseases. Nonoverlapping Bayesian credible intervals demonstrate that the variance attributed to QOD site was greater than the nested variance attributed to surgeon ID for the included PROs. Conclusion: This study presents a novel strategy for the risk-adjusted, PRO-based ranking of spine surgeons and practices. This can help identify positive and negative outliers, thereby forming the basis for large-scale quality improvement. Assuming adequate coverage of baseline risk adjustment, the choice of surgeon matters when considering PROs after lumbar surgery; however, the choice of site appears to matter more. Level of Evidence: 3 Abstract : This study presents a scheme for PRO-based, risk-adjusted rankings of spine surgeons and sites that perform elective lumbar surgery, using the Quality and Outcomes Database (QOD). Assuming adequate coverage of risk adjustment, the choice of surgeon matters when considering PROs, however the choice of site appears to matter more.